Understanding rural Chinese consumers' behavior: Stimulus-organism-response (S-O-R) perspective on Huawei's brand loyalty in China - Zhiyuan Yu; Worasak Klongthong; Jakkrit Thavorn; Chittipa Ngamkroeckjoti (Cogent Business & Management, 2021)
This study examined the effect of familiarity with the Huawei smartphone brand as a mediator between brand involvement and brand loyalty in China and explored behavioral and attitudinal loyalty as two major components of brand loyalty. An exploratory mixed-methods design grounded in the stimulus-organism-response (S-O-R) framework entailed two rounds interviews to build a hypothetical framework, following which 403 Chinese smartphone users were surveyed to test the hypotheses. The results of structural equation modeling (SEM) to analyze the relationship between brand involvement, brand familiarity, and brand loyalty demonstrate that brand involvement exerted a direct effect of approximately 67% on brand familiarity, which in turn had a direct effect of influencing 47% of the variance in brand loyalty. Both brand familiarity and brand involvement had positive and statistically significant effects on brand loyalty; however, the effect of brand familiarity was stronger than that of brand involvement, and the former mediated the relationship between the other two variables.
Keywords: 650; Brand loyalty; brand involvement; brand familiarity; stimulus-organism-response model; smartphone; China